Advanced Technology Related to Radar Signal, Imaging, and Radar Cross-Section Measurement - Kobayashi, Hirokazu; Moriyama, Toshifumi (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Radar-related technology is mainly processed within the time and frequency domains but, at the same time, is a multi-dimensional integrated system including a spatial domain for transmitting and receiving electromagnetic waves. As a result of the enormous technological advancements of the pioneers actively discussed in this book, research and development in multi-dimensional undeveloped areas is expected to continue. This book contains state-of-the-art work that should guide your research.